2019
DOI: 10.4103/aer.aer_47_19
|View full text |Cite
|
Sign up to set email alerts
|

Root cause analysis of blunders in anesthesia

Abstract: The frequency of blunders perioperative because of anesthesia is expanding, and the precise occurrence is significantly thought little of practically due to underreporting. Root cause analysis of majority of anesthesia errors due to lack of knowledge, unfollow the patient procedures and guidelines, medications errors and lack of communication between the members of anesthesia team leading to morbidity or even mortality. The cornerstone in the operating room environment is the communication, especially the pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Consensus points to medication errors as the most prevalent, with frequencies ranging from 0.075% to 0.7%. [ 3 ] In India, a study pinpointed the pressure to expedite tasks as a significant contributor to medication errors in the operating room. [ 4 ] Human error emerges as a dominant factor, implicated in over 80% of critical incidents in anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Consensus points to medication errors as the most prevalent, with frequencies ranging from 0.075% to 0.7%. [ 3 ] In India, a study pinpointed the pressure to expedite tasks as a significant contributor to medication errors in the operating room. [ 4 ] Human error emerges as a dominant factor, implicated in over 80% of critical incidents in anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…[40] Misidentifying syringes because of poor labeling is common in the literature. [41,42] In addition to poor labeling, our respondents identified poor communication to have contributed to 48% of errors. Leonard et al [43] analyzed 2400 adverse events and found that ineffective communication contributed to 70% of them.…”
Section: Factors Causing Medication Errorsmentioning
confidence: 92%
“…RCA on the most frequent errors occurring in anesthesia cases of complex procedures were found to be fine skills of the experts and knowledge deficiencies, poor time management, lack of communication, unfamiliarity with the equipment, and drug-related errors [27]. RCA has also been used to identify the causes of myocardial infarction deaths [28].…”
Section: Quality Monitoring and Turnaround Timementioning
confidence: 99%